Contribution of the outer surface proteins of Borrelia burgdorferi s.l. to the pathogenesis of Lyme disease - Jonsson, Maria (Umeå universitet, Mikrobiologi, 1994)
Borrelia burgdorferi s. l. is a spirochete which causes the multisystemic disorder Lyme disease. As the borreliae lack toxin production, the pathogenicity is thought to involve, at least in part, molecules from the outer surface. Most Lyme disease Borrelia strains express two major outer surface lipoproteins, OspA (31 kD) and OspB (34 kD), on their surface. However, some strains lack the expression of OspA and OspB, but express a smaller 21 to 25 kD OspC protein instead. This thesis focuses on the importance of these proteins in the pathogenesis of Lyme disease. Biochemical and immunochemical studies of the OspA and OspB proteins from strains of various geographic origins show considerable differences in the apparent molecular weights and in their reactivities to monoclonal antibodies. The cloning and sequencing of the ospAB opérons from strains of different origins has demonstrated that the heterogeneity is found also at the DNA level Comparison of the ospAB sequences allows the classification of the strains into three types, which coincide with the recent species designations, B. burgdorferi sensu stricto, B. afzelii and B. garinii The genes are located on a linear plasmid about 50 kb in size, and are cotranscribed as a single message. The expression of the osp operon in different strains was studied by Western blot and Northern blot analysis. The ospAB operon of strains expressing varying amounts of the Osp proteins was cloned and sequenced. The DNA sequence was found to be >99% identical. The regulation appears to be primarily at the transcriptional level. In patients who have received incomplete treatment, B. burgdorferi have been isolated several years after the onset of the disease. As mentioned above, the ospAB loci of different strains show considerable heterogeneity, and it has been speculated that the spirochetes evade the host’s immune system by antigenic variation of the Osp proteins. In a mouse model system it was shown that no variation of the osp genes occurs over the course of an infection, and that other escape mechanisms must be used. The OspB proteins in particular have been shown to be very heterogeneous in different isolates. The MAb 84C recognizes a wide variety of B. burgdorferi strains, and the binding epitope was mapped to a conserved region in the carboxyl terminus of the OspB protein with putative structural and/or functional importance. It is well known that antibodies can kill bacteria in the presence of complement and phagocytes. Some antibodies seem to have a bactericidal effect by themselves. H6831 is a monoclonal antibody recognizing the OspB protein of some B. burgdorferi strains. The bactericidal action of univalent FAb fragments from H6831 was further characterized, and the binding epitope was mapped to a very heterogeneous region of the carboxyl end of the OspB protein. === Diss. (sammanfattning) Umeå : Umeå universitet, 1994, härtill 5 uppsatser === digitalisering@umu